Effects of nitrogen fertilization in shrub willow short rotation coppice production – a quantitative review. Issue 8 (6th April 2018) - Fabio, Eric S.; Smart, Lawrence B.
Abstract: Sustained interest in producing renewable energy from dedicated woody biomass crops, such as shrub willow ( Salix spp.), through short rotation coppice (SRC) has resulted in a substantial amount of published research on SRC over the past few decades. One area of constant focus has been the nutritional requirements for optimal growth and yield. Inconsistency in the results of individual research trials has likely been a driver of repeated experimentation. This review is intended to provide a quantitative examination of the effect of fertilization treatments on willow biomass yield in field conditions. Data from the literature were collected and summarized to test for significant sources of variation in willow biomass nitrogen (N) pools of common SRC genotypes used in North American and European research programs. A meta‐analysis was conducted on studies comparing synthetic or organic sources of N willow fertilization to an unfertilized control treatment to test for yield response. Overall, the majority of responses to fertilization were positive, although variation by species, N source material, and crop age were found. While no clear pattern in N dosage response was observed, the level of yield response was correlated with geographic and climatic variables. Nitrogen export levels were fairly predictable, and the synthesis presented here can be used to refine current guidelines. Environmental and economic aspects are also considered. Abstract : A literature review and meta‐analysis were conducted to assess the current state of knowledge on the effects of nitrogen fertilization on shrub willow yields in North America and Europe. Overall there was a 40% increase in yield, with the majority of responses to fertilization being positive, although variation by species, N source material and crop age was observed. While no clear pattern in fertilizer dosage response was found, nitrogen export at harvest were fairly predictable.